Influencer Marketing and Its Psychological Impact on Youth: A Study on Buying Behavior and Self-Perception - Bhandari, Samikshya; Thapa, Simran (DAV Research Journal, 2026)
This paper aims to examine how influencer marketing affects influencer based decision making behavior in Nepal by analyzing key factors such as influencer engagement, self-perception, financial behavior, and trust in influencer authenticity. It also explores how psychological processes like para-social interaction and wishful identification shape buying decisions and self-image. A descriptive and causal research design was employed. Data were collected through structured questionnaires from 216 digitally active youth in Nepal. The study used SPSS for correlation, regression, and mediation analysis. The results reveal that self-perception, financial behavior, and influencer engagement significantly influence decision-making behavior. Trust, while not directly significant, affects behavior indirectly through self-perception. Self-perception emerged as the strongest predictor. Influencer marketing does not operate merely as a promotional tool but plays a substantial role in shaping youth identity, financial habits, and emotional response. Its impact is both behavioral and psychological. The findings offer practical insights for educators, marketers, and policymakers. Promoting media literacy, responsible influencer practices, and early financial education can mitigate negative outcomes. A holistic approach is essential. This study offers a context-specific framework for understanding influencer marketing’s influence on youth in a developing digital economy. It highlights the indirect mechanisms through which influence is exerted.